Парламентские выборы 1935 г. в Волынском воеводстве - Ким, Игорь; Kim, I. (Волинський національний університет імені Лесі Українки, 2012)
Избирательная кампания и парламентские выборы 1935 года на территории Волынского воеводства имели свою специфику, прежде всего, зависевшую от национального и религиозного состава населения воеводства. Власти и проправительственный лагерь стремясь к получению благоприятного для себя результата на выборах, вынуждены были учитывать отношение к выборам политических партий, польского, украинского и еврейского населения. The election campaign and parliamen-tary elections in 1935 in the Volyn wojewodship had its own specificity, primarily depended on ethnic and religious composition of the province. Authorities and pro-governmental camp trying to obtain a favorable result for myself in the elections, had to take into account the ratio of the elections political parties, Polish, Ukrainian and Jewish population.
Parliamentary Elections in 1935 in the Volyn Wojewodship
Keywords: история Польши; Волынь; режим санации; парламентские выборы 1935 года в Польше; history of Poland; Volyn; sanacja regime; the parliamentary elections in 1935 in Poland.